Forecasting the onset of monsoon over Kerala using the peak in pre-monsoon convective activity over south peninsular India (MAUSAM, 2003)
The role of low-frequency oscillations in the northward movement of the Equatorial Trough during pre-monsoon period over extreme south peninsular India is studied in relation to the associated enhancement of meso-scale convective activities over the region. Main objective of the present study is to bring out usefulness of this information in predicting the onset of summer monsoon over Kerala, well in advance. Thunderstorm data of selected stations over south peninsular India for the months March-June and for the years 1961-92 have been used in this analysis. A characteristic peak in weekly cumulative thunderstorm frequency is seen over these stations about 5-8 weeks prior to the onset of monsoon almost every year, suggesting the dominance of 30-60 day oscillation in the convection associated with these two events. A regression equation has been developed to predict the onset date. The relationship is found to be significant at 0.1% level. The results have been validated using an independent data set of five recent years. A characteristic fall in OLR values over the region, well in correspondence with the characteristic peak in thunderstorm activity suggests that OLR also can be used as a supporting tool in identifying such signal which is useful for the  onset prediction.